2018
DOI: 10.1093/geroni/igy023.260
|View full text |Cite
|
Sign up to set email alerts
|

A Gis Approach to Identifying Service Access Disparities in Rural Appalachia

Abstract: Formal service use can help decrease caregiving burden for family members of persons with dementia; however, barriers related to service use are common. For example, driving distance can be problematic in rural areas with mountainous terrain, as in the Appalachian region of Virginia. The purpose of this study was to examine distance from family homes to services and its association with service use. Thirty-nine caregivers’ residences and 84 service locations were mapped, then driving distance to and distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nevertheless, our findings revealed that communities demonstrated resourcefulness in striving to continue meeting CG and PwD needs (e.g., meal delivery program, telehealth) and sustaining CGs’ ability to continue providing care for PwD. Even beyond the pandemic, home-delivered and internet-based services are convenient for rural families who must travel 45–60 min for specialty care clinics and sometimes basic services like banking and pharmacy ( Harris et al, 2018 ). Expansion of broadband internet service to rural communities is essential both for managing the current pandemic with an uncertain length of restricted movement and for fostering preparedness for future challenges ( Friedenberger, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, our findings revealed that communities demonstrated resourcefulness in striving to continue meeting CG and PwD needs (e.g., meal delivery program, telehealth) and sustaining CGs’ ability to continue providing care for PwD. Even beyond the pandemic, home-delivered and internet-based services are convenient for rural families who must travel 45–60 min for specialty care clinics and sometimes basic services like banking and pharmacy ( Harris et al, 2018 ). Expansion of broadband internet service to rural communities is essential both for managing the current pandemic with an uncertain length of restricted movement and for fostering preparedness for future challenges ( Friedenberger, 2020 ).…”
Section: Discussionmentioning
confidence: 98%